2007
DOI: 10.1590/s1517-83822007000300032
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of Shiga toxin-producing Escherichia coli (STEC) strains in ground beef in São Paulo, Brazil

Abstract: This study aims to assess the prevalence of Shiga toxin-producing Escherichia coli (STEC) in ground beef collected in two cities located in the State of São Paulo, Brazil. A total of 250 samples of raw ground beef were collected in local grocery stores during the period of March to December 2002 in the cities of Ribeirão Preto (114 samples) and Campinas (136 samples), São Paulo State, Brazil. The samples were processed according to standard methods. The resulting 591 E.coli colonies were screened for STEC by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 25 publications
2
4
2
7
Order By: Relevance
“…When analyzed by m-PCR, 46 STEC isolates (15.9%) harbored the stx2 gene, 24 isolates carried (8.3%) stx1 and 15 isolates (5.2%) had both genes. This result differed from a previous report (Bergamini et al, 2007) that showed the dominance of the stx1 gene in cattle. However, other studies have shown agreement with our study (Zschöck et al, 2000).…”
Section: Discussioncontrasting
confidence: 99%
“…When analyzed by m-PCR, 46 STEC isolates (15.9%) harbored the stx2 gene, 24 isolates carried (8.3%) stx1 and 15 isolates (5.2%) had both genes. This result differed from a previous report (Bergamini et al, 2007) that showed the dominance of the stx1 gene in cattle. However, other studies have shown agreement with our study (Zschöck et al, 2000).…”
Section: Discussioncontrasting
confidence: 99%
“…In Brazil, meat and meat products are the most common foods investigated for the presence of STEC. The percentage of meat and meat products contaminated by STEC ranged from 0 to 20·4% (Cerqueira et al ; Rigobelo et al ; Bergamini et al ; Rodolpho and Marin, ; Rigobelo et al ; Lucatelli ; Loiko et al ; Peresi et al ; Ristori et al ; Castro et al ). However, we highlight the study by Santos et al (), which observed that 80% of the fresh beef collected in the industry processing line was contaminated with STEC (Table ).…”
Section: Occurrence Of Stec In Foodmentioning
confidence: 99%
“…Another country of South American and one of the largest beef producers in the world, Brazil has a STEC prevalence of 3.5% in meat products sold in retail markets, with all strains being positive for the ehxA gene responsible for the coding of enterohemolysin and Stx2 toxin, the main gene involved in the most severe cases of the disease (Bergamini and others ).…”
Section: Stec Occurrence and Foodborne Outbreaksmentioning
confidence: 99%